Crystal structure and photoluminescence properties of Eu 2+-activated Ba2LiB5O10 phosphors - Wang, Q.; Deng, D.; Xu, S.; Hua, Y.; Huang, L.; Wang, H.; Zhao, S.; Jia, Guohua; Li, C. (2011)
A novel orange-yellow-emitting Ba2LiB5O 10:Eu2+ phosphor has been synthesized by traditional high temperature solid state reaction. A monoclinic crystal structure of Barium lithiumborates Ba2LiB5O10 was verified by the investigation of X-ray diffraction (XRD). The compound crystallizes in the space group of P121/m1(11) (Z = 2) with the unit cell parameters a = 4.414(1) Å, b = 14.576(2) Å, c = 6.697(2) Å and ß = 104.26(2)°. Barium and lithium atoms are located in distorted octahedral and tetrahedral oxygen coordinations, respectively. Upon around 365 nm excitation, the Eu2+-activated Ba2LiB5O10 phosphors exhibit a single broad emission band with the maximum at about 587 nm, due to the 4f65d ? 4f7(8S7/2) transition of Eu2+. This work investigates the relationship between luminescence properties and structural characterization of the Ba2LiB 5O10: Eu2+. This newly developed phosphor shows high potential as a phosphor conversion for white LED applications. © 2011 Elsevier B.V. All rights reserved.